2020
DOI: 10.1016/j.microc.2019.104549
|View full text |Cite
|
Sign up to set email alerts
|

A simple determination of trace mercury concentrations in natural waters using dispersive Micro-Solid phase extraction preconcentration based on functionalized graphene nanosheets

Abstract: , A simple determination of trace mercury concentrations in natural waters using Dispersive Micro-Solid Phase Extraction preconcentration based on functionalized graphene nanosheets,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…The developed Hg 2+ –SE offers much better features than the electrodes mentioned in the comparison. Moreover, the analytical performance of the proposed electrode in terms of sensitivity, recovery, and linear concentration range was compared with different analytical techniques [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. The Hg 2+ –SE designed in the present study provides better performance than some of the methods mentioned in Table 6 without the need to use the extraction or preconcentration methodology.…”
Section: Resultsmentioning
confidence: 99%
“…The developed Hg 2+ –SE offers much better features than the electrodes mentioned in the comparison. Moreover, the analytical performance of the proposed electrode in terms of sensitivity, recovery, and linear concentration range was compared with different analytical techniques [ 63 , 64 , 65 , 66 , 67 , 68 , 69 ]. The Hg 2+ –SE designed in the present study provides better performance than some of the methods mentioned in Table 6 without the need to use the extraction or preconcentration methodology.…”
Section: Resultsmentioning
confidence: 99%
“…It has been already reported that the N-doped carbon materials can adsorb bacteria more efficiently in comparison to the non-doped carbon [ 26 ], which indicated possible applications of these materials in the water treatment technology. Carbon materials are widely used as sorbents in disinfection systems on both home and technological scale [ 27 ] and some recently published studies showed, that dopants can significantly alter the technological properties of the carbon materials [ 28 , 29 ]. However, as it was also highlighted [ 26 ], the adhesion of bacteria to the N-doped carbon leads to the biofilm formation which is detrimental in the water treatment systems.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the bio-accumulation of mercury, the focus on determining and extracting very low concentrations of mercury has been increasing [20][21][22][23]. Thus, this requires the development of materials with high selectivity and high surface areas to remove mercury from environmental samples at the ultra-trace concentration within the presence of many interfering substances.…”
Section: Introductionmentioning
confidence: 99%